Syzygium cumini Nectar Supplementation Reduced Biomarkers of Oxidative Stress, Muscle Damage, and Improved Psychological Response in Highly Trained Young Handball Players - Assunção Carvalho, Layanna Cibelle de Sousa; de Freitas, Marcelo Conrado; Silva, Alexandre Sergio; Biasoto, Aline Camarão Telles; Martins, Maria do Carmo de Carvalho e; de Moura, Rayane Carvalho; Brito, Ana Karolinne da Silva; Silva, Acacio Salvador Veras e; Ribeiro, Sérgio Luiz Galan; Rossi, Fabrício Eduardo; Santos, Marcos Antônio Pereira dos (Frontiers in Physiology, 2018)
The purpose of this study was to investigate the effects of Syzygium cumini (SC) nectar supplementation on performance, markers of oxidative stress, muscle damage, and psychological response in Handball players. Twenty-five young athletes (age = 18.6 ± 2.4 years) from an elite high school national level Brazilian Handball team were randomized into two study groups: Syzygium Cumini/Jamelon nectar (SC, n = 12) and Placebo (n= 13). The subjects ingested 10 mL/Kg/day of Jamelon nectar or placebo 30 minutes before the training sessions and immediately after training cessation, for 28 days. Body mass index (BMI) and percentage of fat mass were assessed using bioelectrical impedance analysis. Biomarkers of oxidative stress were measured by lipid peroxidation, which was quantified by malondialdehyde (MDA). Total antioxidant capacity (TAC), creatine kinase (CK) activity, and lactate dehydrogenase (LDH) were determined. The 20 m Shuttle Run Test, vertical jump, and Running Anaerobic Sprint Test were assessed to verify performance and the fatigue index was calculated. The Profile of Mood States (POMS) questionnaire was used for psychological evaluation. Both groups demonstrated improved vertical jump performance and a decreased fatigue index over time but without significant differences between them regarding performance. There was statistically significance only for SC in CK, LDH and MDA, and TAC was greater in the SC compared to placebo. Furthermore, only the SC group demonstrated improved mood disturbance and confusion after the intervention. In conclusion, the present study suggests that syzygium cumini nectar supplementation reduced biomarkers of oxidative stress and muscle damage, and improved psychological response in young handball players.